Completely Intracorporeal Robotic-Assisted Laparoscopic Ileovesicostomy - MaryEllen T. Dolat; Greg Wade; B. Mayer Grob; Lance J. Hampton; Adam P. Klausner (Case Reports in Urology)
We present a report of a completely intracorporeal robotic-assisted laparoscopic ileovesicostomy with long term follow-up. The patient was a 55-year-old man with paraplegia secondary to tropical spastic paresis resulting neurogenic bladder dysfunction. The procedure was performed using a da Vinci Surgical system (Intuitive Surgical, Sunnyvale, CA) and took 330 minutes with an estimated blood loss of 100 mL. The patient recovered without perioperative complications. He continues to have low pressure drainage without urethral incontinence over two years postoperatively.